2021
DOI: 10.1029/2020jd033833
|View full text |Cite
|
Sign up to set email alerts
|

How Should Snowball Earth Deglaciation Start

Abstract: Once Earth enters a snowball Earth state (e.g., Hoffman et al., 1998, 2017), it is very difficult to recover because the whole globe will be covered by highly reflective snow and ice. Early estimates using energy balance models (EBMs) showed that 0.16-0.29 bar of CO 2 was required to deglaciate the Neoproterozoic (1,000-541 Ma) snowball Earth (Caldeira & Kasting, 1992; Tajika, 2003). Later studies using general circulation models (GCMs) obtained similar results, i.e., greater than 0.1 bar of CO 2 was required … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, several other processes may be occurring, such as the presence of melt ponds (Wu et al, 2021) and regions of net sublimation (Warren et al, 2002), particularly around the tropics, which suggested albedo may not have been greater than 0.4 -which still translates into a global temperature 16°C lower than today's-(Fig1. Ice-Snow).…”
Section: Millions Of Years: Cryosphere and Snowball Earthmentioning
confidence: 99%
“…However, several other processes may be occurring, such as the presence of melt ponds (Wu et al, 2021) and regions of net sublimation (Warren et al, 2002), particularly around the tropics, which suggested albedo may not have been greater than 0.4 -which still translates into a global temperature 16°C lower than today's-(Fig1. Ice-Snow).…”
Section: Millions Of Years: Cryosphere and Snowball Earthmentioning
confidence: 99%
“…The threshold of CO 2 concentration to trigger the deglaciation has been extensively investigated using different energy balance models and global general circulation models (GCMs) (e.g., Abbot et al., 2012, 2013; Caldeira & Kasting, 1992; Hu et al., 2011; Hyde et al., 2000; Pierrehumbert, 2004; Pierrehumbert et al., 2011; Tajika, 2003). However, the obtained CO 2 thresholds vary from 0.01 to 0.4 bar because of divergent treatments of several processes, for example, ice/snow albedo (Pierrehumbert et al., 2011), cloud parameterization (Abbot, 2014; Abbot et al., 2012), surface dust or aerosols (Abbot & Halevy, 2010; Abbot & Pierrehumbert, 2010; de Vrese et al., 2021), atmospheric pressure (Edkins & Davies, 2021), melt ponds (Wu et al., 2020), and vertical resolution of sea ice model (Abbot et al., 2010).…”
Section: Introductionmentioning
confidence: 99%